2018
DOI: 10.1007/s12035-018-1290-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models

Abstract: Williams syndrome (WS) and 7q11.23 duplication syndrome (Dup7q11.23) are neurodevelopmental disorders caused by the deletion and duplication, respectively, of ~ 25 protein-coding genes on chromosome 7q11.23. The general transcription factor 2I (GTF2I, protein TFII-I) is one of these proteins and has been implicated in the neurodevelopmental phenotypes of WS and Dup7q11.23. Here, we investigated the effect of copy number alterations in Gtf2i on neuronal maturation and intracellular calcium entry mechanisms know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Therefore, western blotting was performed on the first and seventh days after ORIF to evaluate the membrane expression of the GABA A R α1 subunit. Cadherin was used as positive control membrane marker (42,43). There was no difference in the expression of GABA A R α1 between Group C and Group IP 1 on day 1 (C vs. (Figure 3).…”
Section: Combinationmentioning
confidence: 92%
“…Therefore, western blotting was performed on the first and seventh days after ORIF to evaluate the membrane expression of the GABA A R α1 subunit. Cadherin was used as positive control membrane marker (42,43). There was no difference in the expression of GABA A R α1 between Group C and Group IP 1 on day 1 (C vs. (Figure 3).…”
Section: Combinationmentioning
confidence: 92%
“…Finally, as another gene in the 7q11.23 Williams syndrome critical region, specifically the GTF2I gene, has also been linked to brain development and intellectual abilities (Morris et al, 2003;Ghaffari et al, 2018;Deurloo et al, 2019), we repeated our analyses in the general population samples with a SNP in the GTF2I gene previously associated with brain functioning, rs2527367 (Jabbi et al, 2015). This SNP is in high linkage disequilibrium with a number of other GTF2I SNPs between chromosomal location 73706683 and 73777987, and thus obviates the need to investigate a number of related GTF2I SNPs and minimizes the number of statistical procedures necessary (Jabbi et al, 2015).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Recent studies have also demonstrated that GTF2I is involved in neurodevelopment [33,34]. Importantly, the phenotype observed in mice mirrors that observed in humans [35].…”
Section: Spatiotemporal Network Identified Driver Gene and The Gtf2imentioning
confidence: 74%